Answer:
Step-by-step explanation: To find the original length of the rope, we can solve the equation x - 8 1/6 = 5/6, where x represents the original length.
To solve the equation, we need to isolate x on one side of the equation. Let's begin by adding 8 1/6 to both sides:
x - 8 1/6 + 8 1/6 = 5/6 + 8 1/6
Simplifying, we get:
x = 5/6 + 8 1/6
Next, we need to convert the mixed number 8 1/6 to an improper fraction. To do this, we multiply the whole number (8) by the denominator (6) and add the numerator (1). This gives us:
8 × 6 + 1 = 48 + 1 = 49
So, 8 1/6 is equivalent to 49/6.
Substituting this value back into the equation, we have:
x = 5/6 + 49/6
To add the fractions, we need a common denominator, which is 6. So, we rewrite the equation as:
x = (5 + 49)/6
Adding the numerators, we get:
x = 54/6
Simplifying the fraction, we divide the numerator by the denominator:
x = 9
Therefore, the original length of the rope was 9 feet.
The correct answer is:
9 feet